2017
DOI: 10.1021/acs.jnatprod.6b00878
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites from the Plant Endophytic Fungus Aspergillus sp. CPCC 400735 and Their Anti-HIV Activities

Abstract: Thirty-three metabolites including five phenalenone derivatives (1-5), seven cytochalasins (6-12), thirteen butenolides (13-25), and eight phenyl derivatives (26-33) were isolated from Aspergillus sp. CPCC 400735 cultured on rice. The structures of all compounds were elucidated by NMR, MS, and CD experiments, of which 1-5 (asperphenalenones A-E), 6 (aspochalasin R), and 13 (aspulvinone R) were identified as new compounds. Specifically, asperphenalenones A-E (1-5) represent an unusual structure composed of a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 23 publications
2
58
1
2
Order By: Relevance
“…In our study, bulgarialactone B (1) revealed no cytotoxicity against the tested L5178Y cell line, albeit in a previous study it was reported to possess antitumor activity against an ascitic ovarian carcinoma xenogra. 30 Butyrolactone analogues similar to the derivatives isolated in this study were previously described from Aspergillus species, 58,62,[66][67][68] Here we report B. inquinans as a source of this type of metabolites for the rst time. Moreover, the results obtained upon application of the OSMAC approach employing a mixture of salts (MgSO 4 , NaNO 3 and NaCl) highlighted the usefulness of this strategy not only for diversifying secondary metabolites produced by this strain, but also to afford rare natural product scaffolds, as exemplied by the isolation of 1,3oxazine derivatives (7 and 8) and of an unusual a-pyrone dimer 13.…”
Section: Resultssupporting
confidence: 55%
“…In our study, bulgarialactone B (1) revealed no cytotoxicity against the tested L5178Y cell line, albeit in a previous study it was reported to possess antitumor activity against an ascitic ovarian carcinoma xenogra. 30 Butyrolactone analogues similar to the derivatives isolated in this study were previously described from Aspergillus species, 58,62,[66][67][68] Here we report B. inquinans as a source of this type of metabolites for the rst time. Moreover, the results obtained upon application of the OSMAC approach employing a mixture of salts (MgSO 4 , NaNO 3 and NaCl) highlighted the usefulness of this strategy not only for diversifying secondary metabolites produced by this strain, but also to afford rare natural product scaffolds, as exemplied by the isolation of 1,3oxazine derivatives (7 and 8) and of an unusual a-pyrone dimer 13.…”
Section: Resultssupporting
confidence: 55%
“…Prominent representatives are the trihydroxypulvinones (Edwards and Gill 1973) isolated from Suillus grevillei or the group of aspulvinones from Aspergillus spp. (Ojima et al 1973;Golding and Rickards 1975;Pang et al 2017). However, substitution of the butenolide unit by a third phenyl group at C-9′ has not been found in nature so far and provides a new subclass of pulvinones.…”
Section: Resultsmentioning
confidence: 99%
“…Many PHs have been described recently to possess different biological activities ranging from antifungal to antiHIV. For example, Li et al [28] described the antifungal activity of some PHs isolated from Auxarthron pseudauxarthron against Cryptococcus and Candida and Pang et al [29] isolated some PHs with antiHIV activity from Aspergillus . Other studies have shown antibacterial activities against many species such as Pseudomonas aeruginosa , Escherichia coli , Staphylococcus aureus and Bacillus subtilis [30].…”
Section: Discussionmentioning
confidence: 99%